Research on a Kind of PLC Based Fuzzy-PID Controller with Adjustable Factor - Wei Xie; Jianmin Duan (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
A kind of fuzzy-PID controller with adjustable factor is designed in this paper. Scale factor’s self-adjust will come true. Fuzzy control algorithm is finished in STEP7 software, and then downloaded in S7-300 PLC. WinCC software will be used to control the change-trend in real time. Data communication between S7-300 PLC and WinCC is achieved by MPI. The research shows that this fuzzy-PID controller has better robust capability and stability. It’s an effective method in controlling complex long time-varying delay systems. DOI:  http://dx.doi.org/10.11591/telkomnika.v14i2.7661